O ENSINO SUPERIOR EM PONTA GROSSA NO CONTEXTO DA EXPANSÃO E INTERIORIZAÇÃO (Revista de História Regional, 2007)
The present article analyses the expansion of the College Education in Brazil, that education politics enabled at the State of Paraná to develop focused on the creation of the Colleges in the hinterland at the end of the 1940s, when the Philosophy, Sciences and Letters College of the State of Paraná, in Ponta Grossa, was created, process which was completed in the beginning of the 70swith the installation of the State University in Ponta Grossa and also other Universities in Londrina and Maringá, installed on the Northern part of the state.